2015
DOI: 10.1515/amm-2015-0092
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Coating To Realize Desired Pore Characteristics Of Sintered Diatomite Membrane

Abstract: Porous ceramic membranes prepared from natural materials such as diatomite, have lately attracted great interest in industrial applications due to their cost-effectiveness. In this study, we attempted to prepare an alumina coating to be deposited over a sintered diatomite-kaolin composite support layer in order to reduce the largest pore size to below 0.4 µm; such a coating could be potentially used in water treatment applications for bacterial removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Various types of porous diatomite-kaolin composites fabricated by different preparation methods have been described in our previous studies [12,[20][21][22][23][24][25][26][27][28][29][30][31] and in those of other research groups [32][33][34][35][36]. However, to the best of our knowledge, only a few have focused on the detailed preparation and characterization of reticulated porous diatomite-kaolin composites, besides our previous report that discussed the feasibility [3].…”
Section: Introductionmentioning
confidence: 97%
“…Various types of porous diatomite-kaolin composites fabricated by different preparation methods have been described in our previous studies [12,[20][21][22][23][24][25][26][27][28][29][30][31] and in those of other research groups [32][33][34][35][36]. However, to the best of our knowledge, only a few have focused on the detailed preparation and characterization of reticulated porous diatomite-kaolin composites, besides our previous report that discussed the feasibility [3].…”
Section: Introductionmentioning
confidence: 97%
“…(4) We determined the air permeability of the diatomite-kaolin composite-coated diatomite-kaolin composite support layer [17]. (5) the air permeability of an alumina-coated diatomitekaolin composite support layer [15,16,18], along with (6) the water permeability (using pure water) and rejection rate (using ISO 12103-1 A3 test dust) of a diatomite-kaolin composite support layer [13]. Finally, and most notably, (7) we evaluated the water permeability (using pure water) and the reliability of the aluminacoated diatomite-kaolin composite support layer were determined.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical strength of a diatomite support layer is not acceptable for a free-standing membrane, therefore, we introduced kaolin to tailor the pore characteristics of the diatomite support layer. Previously, we reported possible approaches for fabrication of a diatomite-based support layer that allowed fine-tuning of the pore characteristics [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions and basic properties of diatomite have been comprehensively explained in previous reports [18][19][20][21][22][23][24][25][26][27][28][29][30]. Recently, the authors reported several types of porous diatomite such as (1) uniaxially-pressed diatomite-based support layers for microfiltration [18][19][20][21][22][23][24][25][26][27], (2) extruded diatomite-based support layers for microfiltration [28,29], and (3) particle-stabilized diatomite foam with a bimodal pore structure [30]. However, to the best of author's knowledge, there are no studies on the preparation and characterizations of reticulated porous diatomite-kaolin composite.…”
Section: Introductionmentioning
confidence: 99%